STRATEGI PENGENAAN BIAYA PENARIKAN DI COUNTER TELLER UNTUK MENGURANGI ANTRIAN DI PT. BANK MANDIRI (PERSERO) TBK - Irfan Firdian Herlambang (Sainteks: Jurnal Sain dan Teknik, 2019)
Imposition Strategy Withdrawal Fees at Counter Teller can Reduce Queue Length at PT Bank Mandiri (Persero) Tbk. This study was conducted to intend the application of the queue strategy at PT Bank Mandiri (Persero) Tbk also to see the supporting factors of this strategy. As the Bank with the largest assets, Bank Mandiri, must take serious to manage these assets in order to become the most profitable company. With the growing number of customers from year to year, management must find the way to overcoming a queue that will not be accommodated for a long time, especially for small branches that have large customers. Companies must be able to anticipate this because competitors will do the same. The company wish that the new strategy will make customers more comfortable to become BANK Mandiri customers. PT Bank Mandiri (Persero) Tbk will continue to monitor market developments so that the company is still leading from its competitors and it is expected that in the future the company will be able to have more value than other banks.